ANALISIS PROBLEMATIKA KETERAMPILAN BELAJAR SISWA SMP MELALUI INSTRUMEN AUM PTSDL: STUDI KASUS PENGABDIAN MASYARAKAT DI DESA LUBUK CEMARA - Najwa Nadhira Harahap; Alfin Siregar; Rizky Nur Zannah Pardede; Nazwa Azzahra; Dilla Bunaiya (DEVELOPMENT: Journal of Community Engagement, 2026)
Learning challenges in rural areas are often overlooked in educational literature, yet identifying student needs is the foundation for targeted guidance and counseling interventions. This study aims to identify and analyze learning barriers faced by junior high school students in Lubuk Cemara Village and to formulate proactive guidance and counseling strategies. A quantitative descriptive approach was used in this study, involving 32 eighth-grade students as research subjects. Data were collected using the PTSDL series Problem-Uncovering Tool (AUM) and processed using descriptive analysis techniques to map the distribution of problems across five main components. The results showed that student learning challenges were dominated by technical barriers in the Learning Skills aspect with an average score of 75.6, and structural barriers in the Learning Facilities and Environment aspects with average scores of 13.3 and 22.1, respectively. These findings confirm that the main obstacles for students lie not in intellectual capacity, but rather in methodological unpreparedness and limited supporting ecosystems. The implications of this study require a paradigm shift in guidance and counseling services from a responsive to a proactive-preventive approach through strengthening learning literacy techniques, advocating for the provision of learning facilities, and providing psychoeducation to parents regarding the creation of a conducive domestic environment. The contribution of this research is the proposed guidance model that bridges the gap between accessibility and academic potential for students in rural areas.